Mechanism analysis and process optimization of acetone–methanol azeotrope separation using 1-ethyl-3-methylimidazolium acetate based mixed extractants. (15th December 2022) - Chen, Zhengrun; Zhang, Yanli; Zhou, Mengjin; Yin, Kexin; Zhou, Yaru; Cui, Peizhe; Zhu, Zhaoyou; Zhong, Limei; Wang, Yinglong
Abstract: The development of high-performance extractants and intensification technologies is crucial for saving energy in the separation of azeotropes by extractive distillation. An effective method for separating azeotropes by extractive distillation using an organic solvent–ionic liquid mixed extractant is proposed. The selectivity and solubility of 96 ionic liquids were calculated based on the conductor-like screening model for real solvents, and the best extractant, 1-ethyl-3-methylimidazolium acetate ([EMIM][AC]), was obtained. The interaction energy, bond length, and independent gradient model based on the Hirshfeld partition between different components and azeotropes were calculated by applying quantum chemistry to analyze the structure–activity relationship between molecules. The results showed that dimethyl sulfoxide has a stronger interaction with methanol than with other organic extractants, [EMIM][AC] + dimethyl sulfoxide is more likely to form hydrogen bonds with methanol, the O atom in dimethyl sulfoxide mainly forms hydrogen bonds with the H atom in methanol, and the H atom in [EMIM][AC] mainly forms hydrogen bonds with the O atom of methanol. In addition, a process for separating acetone–methanol by extractive distillation using a mixed extractant was designed. The minimum total annual cost (TAC) was considered as the objective function, and a sequential iterative optimization algorithm was used to optimize the separation process and obtain the optimal operating parameters. The results showed that the TAC of the extractive distillation process of [EMIM][AC] + dimethyl sulfoxide mixed extractant was 15.00% lower than that of [EMIM][AC] +  N, N -dimethylformamide and 42.10% lower than that of [EMIM][AC] +  N -methylpyrrolidone. In the extractive distillation process, the pollutant gas emissions of [EMIM][AC] + dimethyl sulfoxide decreased by 43.29% compared with those of [EMIM][AC] +  N -methylpyrrolidone and 7.87% compared with those of [EMM][AC] +  N, N -dimethylformamide. Finally, an energy-saving process of vapor-recompression extractive distillation was explored. The results showed that the TAC of vapor-recompression-assisted extractive distillation was 3.98% lower than that of [EMIM][AC] + dimethyl sulfoxide and that the pollutant gas emissions were 20.28% less than those of [EMIM][AC] + dimethyl sulfoxide. This study on the structure–activity relationship of mixed extractants and process optimization provides theoretical guidance for the separation of azeotropes in the industry. Graphical abstract: Image 1 Highlights: A method of separating azeotropes with organic-IL mixed extractant was proposed. The structure-activity relationship between extractant and azeotrope was discussed. The intensification technology of extractive distillation was studied.